PENGARUH E-SERVICE QUALITY DAN TRUST TERHADAP CUSTOMER LOYALTY YANG DIMEDIASI OLEH CUSTOMER SATISFACTION: STUDI KASUS PADA PENGGUNA APLIKASI KESEHATAN: THE EFFECT OF E-SERVICE QUALITY AND TRUST ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION: A CASE STUDY ON HEALTHCARE APP USERS - Muhamad Lutfi Prayitno; Agung Kresnamurti Rivai P; Rahmi Rahmi (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This research aims to examine the effect of e-service quality and trust on customer loyalty of Halodoc application with customer satisfaction as a mediation variable. This type of research is explanatory research that explains the causal relationship between variables through hypothesis testing. The data collection method used a survey method with the instrument in the form of a questionnaire. The sampling technique uses non-probability sampling with a sample size of 200 respondents domiciled in Jakarta and more or equal to 18 years old who have used the Halodoc application service at least twice in the last six months. Data were analyzed using PLS-SEM and assisted by SmartPLS 3.2.9 software. The test results show that there are positive and significant effect on all hypotheses. Those hypotheses are: (1) e-service quality variable has a positive and significant effect on customer loyalty, (2) trust variable has a positive and significant effect on customer loyalty, (3) e-service quality variable has a positive and significant effect on customer satisfaction, (4) trust variable has a positive and significant effect on customer satisfaction, (5) customer satisfaction has a positive and significant effect on customer loyalty, (6) e-service quality variable has a positive and significant effect on customer loyalty mediated by customer satisfaction, and (7) trust variable has a positive and significant effect on customer loyalty mediated by customer satisfaction